Myth, logos, and ecology: Local community perception of social signs on the slopes of Semeru Mountain post-disaster - Setiyawan, Radius; Wahyuni, Holy Ichda; Romadhon, Nur Hidayatullah; Sari, Adelin Aprilia (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Seeing a social sign, results in striving to derive the meaning from the sign when it is used. One of the events that appear in various types of social sign is a disaster. It creates various myths that also act as a social sign; one of them is a myth about the relationship between humans and nature. This study aims to explain the perception of the local community in the Sumber Mujur village of Semeru Mountain Slope about social signs made as myth postdisaster eruption in 2022. The myth that is believed by the local community proved to have relevance to ecological sustainability. This research uses qualitative methods through deep interviewing technique. Informants in this study are a local community in the Semeru Mountain area, East Java which is part of the 2021 Semeru eruption survivors. Based on existing findings, most myths grow in line with a scientific view. Although the background or ways of working is different, myth and logos have compatible relevance in the context of ecology sustainability. This study concludes that myths give impact on society's attitude so as to maintain ecological sustainability, as well as a form of cultural adaptation, both in terms of conservation awareness and mitigation.